Fallopian tubal histogenesis of ovarian endometriosis—A study of folate receptor-alpha expression - Wang, Yiying; Li, Qiyan; Zhao, Ruijiao; Wang, Jerry Y.; Wang, Yan; Lin, Wanrun; Yuan, Zeng; Zhang, Jing; Fadare, Oluwole; Wang, Yue; Zheng, Wenxin (Frontiers in Medicine, 2023)
Background Ovary is a common organ site involved by endometriosis. We previously found that fallopian tube may contribute to the histogenesis of ovarian endometriosis. The finding was novel and requires further studies. We addressed this issue by examining a differentially expressed gene folate receptor alpha (FOLR1) and its protein (FRA) in this study. Results A total of 144 tissue samples were studied. These included 32-paired tubal-endometrial-ovarian endometriosis samples (n = 96), 18 samples of ovarian endometriosis without corresponding fallopian tube or endometrium, and 30 ovarian tissue samples with ovarian surface epithelia but without endometriosis. Multiple comparisons among groups of ovarian endometriosis, normal fallopian tube and benign endometrium were performed. FOLR1 was highly expressed in the epithelia of fallopian tube and ovarian endometriosis, with paired endometrial samples showing a significantly lower level of expression. Similar differential studies for FRA protein were performed through Western blot and immunohistochemistry (IHC). The expression of folate receptor alpha at both mRNA and protein levels in the tissues (fallopian tube or ovarian endometriosis vs. the endometrium) were significantly different (p < 0.001). All ovarian surface mesothelial epithelia showed negative expression of FRA by IHC. Conclusions The results further support that the fallopian tube may contribute to the development of ovarian endometriosis. Understanding the tubal contribution to ovarian endometriosis should ultimately contribute to ongoing investigative efforts aimed at identifying alternative ways to prevent and treat endometriosis. High level of FRA expression in the fallopian tube and endometriosis might be considered as potential tissue sites for targeted therapy.